Practice and Preparation Time Facilitate System-Switching in Perceptual Categorization - Hélie, Sébastien (Frontiers in Psychology, 2017)
Mounting evidence suggests that category learning is achieved using different psychological and biological systems. While existing multiple--system theories and models of categorization may disagree about the number or nature of the different systems, all assume that people can switch between systems seamlessly. However, little empirical data has been collected to test this assumption, and recent available data suggest that system--switching is difficult. The main goal of this article is to identify factors influencing the proportion of participants who successfully learn to switch between procedural and declarative systems on a trial--by-trial basis. Specifically, we tested the effects of preparation time and practice, two factors that have been useful in task--switching, in a system--switching experiment. The results suggest that practice and preparation time can be beneficial to system--switching (as calculated by a higher proportion of switchers and lower switch costs), especially when they are jointly present. However, this improved system--switching comes at the cost of a larger button--switch interference when changing the location of the response buttons. The article concludes with a discussion of the implications of these findings for empirical research on system--switching and theoretical work on multiple--systems of category learning.